Transportation of hazardous materials: State and local activities (A special report) (Malabar, Florida, 1988)
This report summarizes Federal programs and identifies three major areas of State and local government concern: prevention and enforcement activities, emergency response and training, and planning and data gathering
Keywords: hazardous substances - united states - transportation